Help-Seeking and Management Behavior of the Deans and Academic Chairpersons in the University of Eastern Philippines - Piczon, Veronica A.; Asis, Leah A. de (International Journal of Emerging Trends in Social Sciences, 2019)
This study investigated the help-seeking and management behavior of Deans and Academic chairpersons in a state university In Northern Samar. It determined the effect of help-seeking behavior on management behavior of the administrators. A total of thirty-two college deans and department heads participated in the study. Colleges administrators admitted that they seek help from others when faced with challenging situations. Findings showed they are participating in decision making efficiently. Similar efficiency level was found on management behavior in terms of problem-solving, conflict management, and crises’ intervention. Overall, management behavior of college school administrators was considered efficient. Help-seeking behavior positively Influenced the problem solving and conflict management abilities of the colleges’ administrators. On the other hand, the test of the relationship between help-seeking behavior and performance of the school administrators showed that only occupational competence had a significant relationship with help-seeking behavior. Schools administrators’ help seeking behavior is much helpful in dealing with their duties particularly on management areas of their occupation. Occupational competence was significantly related to decision making, problem-solving and conflict management. On the other hand, professional and personal characteristics were also significantly, related to crisis intervention. Punctuality and attendance had no significant relationship to any of the management behavior. Lastly, the test of difference in help-seeking behavior of colleges administrators when compared by age and gender showed that help seeking varies among different age groups. Younger colleges administrators seek more help compared to seasoned administrators. No significant difference was found on the help-seeking ability between male and female administrators. Implications of help-seeking on school administrators were discussed.